Development of Micro/Nano Pattern Arrays with Grating-Based Periodic Structures using the Direct Laser Lithography System - Rajan, Rency; Kirubaraj, Alfred; Samson, Senith; Prince, Shajin; Ramson, S.R. Jino (Current Nanoscience, 2025)
Introduction This research delves into utilizing the Direct Laser Lithography System to produce micro/nanopattern arrays with grating-based periodic structures. Initially, refining the variation in periodic structures within these arrays becomes a pivotal pursuit. This demands a deep comprehension of how structural variation aligns with specific applications, particularly in photonics and material science. Methods Advancements in hardware, software, or process optimization techniques hold potential for reaching this objective. Using an optical beam, this system enables the engraving of moderate periodic and quasi-periodic structures, enhancing pattern formation in a three-dimensional environment. Through cost-effective direct-beam interferometry systems utilizing 405 nm GaN and 290 to 780 nm AlInGaN semiconductor laser diodes, patterns ranging from in period were created, employing 300 nm gratings. Results The system's cost-efficiency and ability to achieve high-resolution permit the creation of both regular and irregular grating designs. By employing an optical head assembly from a blu-ray disc recorder, housing a semiconductor laser diode and an objective lens with an NA of 0.85, this system displays promising potential in progressing the fabrication of micro/nanopattern arrays. Conclusion Assessing their optical, mechanical, and electrical properties and exploring potential applications across varied fields like optoelectronics, photovoltaics, sensors, and biomedical devices represent critical strides for further exploration and advancement.
Keywords: Laser interference